A novel phosphor structure for improving the luminous flux of white LEDs - Nguyen Thi Phuong Thao; Jan Nedoma; Le Anh Vu; Dieu An Nguyen Thi (Institute of Advanced Engineering and Science, 2022)
This section focuses on the color uniformity and luminous production of multi-chip white-emitted LED lighting systems (MCW-LEDs) in improving illuminated performance. To accomplish the desired outcome, CaO:Sb3+ must be mixed with their phosphor compounding, which has been shown to have a massive impact on illuminating effectiveness. There is also evidence that the increasing of yellowish-green-emitted phosphorus CaO:Sb3+ concentration supports color homogeneity as well as luminescent effectiveness enhancements in MCW-LEDs featuring a 8500 K correlating colour temperature (CCT). Meanwhile, that rise in CaO:Sb3+ concentration leads to the gradually deteriorating color quality scale. Thus, if appropriate concentration and particle size of CaO:Sb3+ phosphor are determined, it is not hard to obtain such an excellent presentation in color uniformity, color quality scale and luminescence of MCW-LEDs.